Methodology of the Field Administration of Stroke Therapy – Magnesium (FAST-MAG) Phase 3 Trial: Part 1 – Rationale and General Methods. Issue 2 (February 2014) - Saver, Jeffrey L.; Starkman, Sidney; Eckstein, Marc; Stratton, Samuel; Pratt, Frank; Hamilton, Scott; Conwit, Robin; Liebeskind, David S.; Sung, Gene; Sanossian, Nerses; ,
Rationale: Prehospital initiation by paramedics may enable delivery of neuroprotective therapies to stroke patients in the hyperacute period when they are most effective in preclinical studies. Magnesium is neuroprotective in experimental stroke models and has been shown to be safe with signals of potential efficacy when started early after onset of human cerebral ischemia. Aims: (a) To demonstrate that paramedic initiation of the neuroprotective agent magnesium sulfate in the field is an efficacious and safe treatment for acute stroke; (b) To demonstrate that field enrollment of acute stroke patients is a practical and feasible strategy for phase 3 stroke trials, permitting enrollment of greater numbers of patients in hyperacute time windows. Design: Multicenter, randomized, double-blinded, placebo-controlled, pivotal clinical trial. Study Procedures: The study is enrolling 1700 patients (850 in each arm) with likely acute stroke, including both cerebral infarction and intracerebral hemorrhage patients. Inclusion criteria are: (a) likely stroke as identified by the modified Los Angeles Prehospital Stroke Screen (mLAPSS), (b) age 40–95, (c) symptom onset within 2 h of treatment initiation, and (d) deficit present ⩾15 min. Paramedics administer a loading dose of magnesium sulfate (Mg) or matched placebo in the field, 4 grams over 15 min. In the Emergency Department, a maintenance infusion follows, 16 grams Mg or matched placebo over 24 h. Outcomes: The primary endpoint is the modified Rankin Scale measure of global disability, assessed using the Rankin Focused Assessment, 90 days after treatment. Secondary efficacy endpoints include the NIHSS (neurologic deficit), Barthel Index (activities of daily living), and the Stroke Impact Scale (quality of life).